(untitled) (World Bulletin of Social Sciences, 2026)
The United Kingdom’s departure from the European Union (Brexit) has reconfigured its immigration policy and labor market demands, with important implications for migrants from Uzbekistan. This study examines migration trends from Uzbekistan to the UK from 2020–2025, using official statistics, reports, and academic literature. It reviews legal, labor (including seasonal and skilled), student, and other migration categories. Results show a dramatic rise in Uzbek nationals entering the UK under new temporary work schemes: for example, Seasonal Worker visas grew from only 556 in 2021 to 6,278 in 2024[1][2]. Migration flows in this period were heavily shaped by UK labor shortages after Brexit, with 1,900 Uzbeks employed in the UK in 2023 and bilateral agreements on recruitment[3]. Key opportunities include high wages and legal migration channels for Uzbek workers and students, as well as strengthened UK–Uzbek cooperation (e.g. recent memoranda)[4]. Major threats involve migrant exploitation risks, high fees/debts, and precarity due to tied visas[5]. The paper concludes that while Brexit has opened new labor migration routes for Uzbekistan, robust protections and oversight are needed to ensure mutual benefit.